Impaired Interleukin‐27–Mediated Control of CD4+ T Cell Function Impact on Ectopic Lymphoid Structure Formation in Patients With Sjögren's Syndrome. Issue 9 (21st July 2020) - Lucchesi, Davide; Coleby, Rachel; Pontarini, Elena; Prediletto, Edoardo; Rivellese, Felice; Hill, David G.; Derrac Soria, Alicia; Jones, Simon A.; Humphreys, Ian R.; Sutcliffe, Nurhan; Tappuni, Anwar R.; Pitzalis, Costantino; et al.
Abstract : Objective: Ectopic lymphoid structures (ELS) develop at sites of infection, autoimmunity, and cancer. In patients with Sjögren's syndrome (SS), ELS support autoreactive B cell activation and lymphomagenesis. Interleukin‐27 (IL‐27) is a key regulator of adaptive immunity and limits Th17 cell–driven pathology. We undertook this study to elucidate the role of IL‐27 in ELS formation and function in autoimmunity using a murine model of sialadenitis and in patients with SS. Methods: ELS formation was induced in wild‐type and Il27ra − / − mice via salivary gland (SG) cannulation of a replication‐deficient adenovirus in the presence or absence of IL‐17A neutralization. In SG biopsy samples, IL‐27–producing cells were identified by multicolor immunofluorescence microscopy. Lesional and circulating IL‐27 levels were determined by gene expression and enzyme‐linked immunosorbent assay. The in vitro effect of IL‐27 on T cells was assessed using fluorescence‐activated cell sorting and cytokine release. Results: In experimental sialadenitis, Il27ra −/− mice had larger and more hyperactive ELS (focus score; P < 0.001), increased autoimmunity, and an expanded Th17 response ( P < 0.001), compared to wild‐type mice. IL‐17 blockade in Il27ra − / − mice suppressed the aberrant ELS response (B and T cell reduction against control; P < 0.01). SS patients displayed increased circulating IL‐27 levels ( P < 0.01), and in SG biopsy samples, IL‐27 was expressed by DC‐LAMP+ dendritic cells in association with CD3+ T cells. Remarkably, in SS T cells (but not in T cells from patients with rheumatoid arthritis or healthy controls), IL‐27–mediated suppression of IL‐17 secretion was severely impaired and associated with an aberrant interferon‐γ release upon IL‐27 stimulation. Conclusion: Our data indicate that the physiologic ability of IL‐27 to limit the magnitude and function of ELS through control of Th17 cell expansion is severely impaired in SS patients, highlighting a defective immunoregulatory checkpoint in this condition.